Handbook of electrical and electronic insulating materials - Shugg, W. Tillar (IEEE Press, 1995)
Covering virtually all classes of insulating materials for electrical and electronic applications, this handbook offers immediate access to detailed information in one easy-to-use source. Included are major producers, technologies, methods of manufacture, trades, applicable standards and specifications, properties, uses, development programs, and market trends. Complete with a wealth of data and lacking in technical jargon, this book will be invaluable to electrical and electronics engineers who need to make informed choices about dielectric and electrical insulation materials as well as electrical engineering students in need of a comprehensive reference.